Effect of illumination, casein hydrolysate and proline on callus induction of Oryza sativa L. var. MR219 - Che Radziah, C.M.Z.; Siti Nurkhalida, A.K.; Zamri, Z.; Ismanizan, I. (Penerbit Universiti Kebangsaan Malaysia, 2012)
In this study, factors such as illumination, casein hydrolysate and proline were shown to produce high numbers of calli from MR219 mature seeds. The effect of different concentrations (1, 2, 3, 4 and 5 mgL-1) of 2,4-dicholorophenoxy acetic acid (2,4-D) under different illuminations (24 hours light, 16/8 hours photoperiod, dark) on callus induction and growth were investigated. The results revealed that the highest percentage of callus induction (100%) and growth (90%) was observed in the Murashige and Skoog (MS) medium supplemented with 5 mgL-1 2,4-D incubated under 16/8 hours photoperiod. The effect of different concentrations of casein hydrolysate (0, 300, 400, 500, 600, 700, 80 and 1000 mgL-1) and proline (0, 500, 1000 and 1500 mgL-1) on callus induction and growth of MR219 were also studied. It was found that increasing concentrations of casein hydrolysate and proline did not give a significant effect on the percentage of callus induction. However, a significant percentage of callus growth (90%) was recorded when the callus induction medium was supplemented with 1000 mgL-1 proline.